(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article considers the process of secure key exchange based on Elliptic Curve Cryptography (ECC) and the algorithm for encrypting data using this key. In the study, a mechanism for generating a public key of the Diffie–Hellman type based on the operations of adding and multiplying points on an elliptic curve is implemented in the Python programming language. A public secret key is calculated between Alice and Bob by generating public and private keys. The process of encrypting and decrypting text data based on the generated public key is performed using the XOR symmetric algorithm. The proposed model can be an effective tool for explaining the principle of operation of cryptographic protocols, teaching cryptography, and modeling information security systems. The results of the study show the mechanism of operation of elliptic curve cryptography through small-parameter models and help to understand the theoretical foundations of modern secure communication protocols.